The Impact of Ice Massage at SP6 and LI4 Point on Labor Pain and Anxiety : a literature review - Yulizawati, Yulizawati; Intasir, M. pemberdi (Journal of Midwifery, 2024)
Background: A midwife's fundamental care includes lowering anxiety, improving comfort, and managing labor pain. The health of the mother and fetus is adversely affected by some pharmacologic techniques for reducing labor pain. Applying ice massage to acupressure points can have a variety of benefits, including promoting energy flow there and reducing stress and discomfort by activating peripheral nerve receptors. Activating the spleen (SP6) and large intestine (L14) points reduces labor pain and alleviate anxiety. Purpose: The aim of this paper is to review the literature to identify the effect of ice massage on labor pain and anxiety at SP6 and LI4 point. Methods : A narrative review of journal articles was conducted. Databases searched were PubMed and Google Scholar. Search terms used were â€œice massageâ€, â€œlabor painâ€, and â€œanxietyâ€. Limitations included â€˜English languageâ€™and â€˜published between 2000â€“2024. Results : Reviewed for this paper were 10 studies that met the inclusion criteria. Results were categorised using thematic analysis. Themes that emerged were labor pain and anxiety and will be explored under these themes. Conclusions : The impact of ice massage on labor discomfort and anxiety has been covered in this review of the research. Most of the research articles that were used to source this review were conducted at SP6 and LI4 stages and published in clinical trials. The results of the study showed that applying ice massage to the LI4 and SP6 sites reduced labor discomfort. A midwife may think about using ice massage as a technique to lessen anxiety. Midwives can utilize the results of this study to manage labor discomfort.